Surface wave photonic quasicrystal - An, Yinbing (2020)
In developing strategies for manipulating surface electromagnetic waves, it has been recently recognized that a complete forbidden bandgap can exist in a periodic surface-wave photonic crystal, which has subsequently produced various surface-wave photonic devices. However, it is not obvious whether such a concept can be extended to a quasi-periodic surface-wave system that lacks translational symmetry. Here, we experimentally demonstrate that a surface-wave photonic quasicrystal that lacks short-range order can also exhibit a forbidden bandgap for surface electromagnetic waves. The lower cutoff of this forbidden bandgap is mainly determined by the maximum separation between the nearest neighboring pillars. Point defects within this bandgap show distinct properties compared to a periodic photonic crystal in the absence of translational symmetry. A line-defect waveguide, which is crafted out of this surface-wave photonic quasicrystal by shortening a random row of metallic rods, is also demonstrated to guide and bend surface waves around sharp corners along an irregular waveguiding path.